Francophone Muslim intellectuals, Islamic associational life and religious authority in Burkina Faso - (:unkn) unknown (My University, 2020)
The attention paid to the security threats hanging over Burkina Faso, while legitimate, has overshadowed the underlying transformations in Islamic associational life since the fall of President Blaise Compaoré in October 2014. This major political upheaval had a significant impact on the participation of Muslims in socio-political debates, the relations between generations and, more widely, the bases upon which religious authority is claimed. This article analyses the competition for religious leadership between Islamic actors in the public sphere in Burkina Faso by focusing mainly on francophone ‘Muslim intellectuals’. First, the study shows the gap between the gerontocracy at the helm of the main Islamic associations and the Burkinabe youth, which widened throughout the 1990s and 2000s and came strongly to the fore after the popular uprising of October 2014. Second, taking advantage of the space left vacant by traditional community leaders during the transition process, some young francophone ‘Muslim intellectuals’ actively sought to portray themselves as the vehicles of a ‘civil Islam’ and strove to promote new forms of civic engagement through religion. Other Muslim organizations have also tried to take advantage of the new political context to strengthen their presence in the socio-political arena.
Keywords: African Research